Method for preparing high-entropy ceramic coating on titanium alloy surface based on high-speed laser cladding molten pool in-situ reaction
High-entropy ceramic coatings are prepared by performing in-situ reactions on the surface of titanium alloys using high-speed laser cladding technology, which solves the problems of poor forming quality and difficulty in forming high-entropy phases in the existing technology, and achieves high hardness and Excellent performance coating.
Patent Information
- Application Number
- CN202411476319.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to effectively prepare high-entropy ceramic coatings, especially on the surface of titanium alloys, which are limited by the extremely high melting point and complex components of high-entropy ceramic materials.
High -speed laser melting technology is used to prepare high -entropy ceramics coating on the surface of titanium alloy. Through the in situ reaction of the melting pool on the surface of the titanium alloy under high -energy laser beam, high -entropy one boronicides and high -entropy bornefish phase are generated.
The quality and excellent performance of high -entropy ceramic coatings are realized. The average hardness of the coating is as high as 1931.4HV0.5, which has good protection, enhanced effects and high temperature antioxidant performance.
Smart Images

Figure CN119352011A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite protective coatings on titanium alloy surfaces, and specifically relates to a method for preparing a high-entropy ceramic coating by high-speed laser cladding based on in-situ reaction of a molten pool on the surface of a titanium alloy under a high-energy laser beam. Background Art
[0002] Since the high entropy material was proposed in 2004, it has shown excellent performance in the fields of corrosion resistance, wear resistance, and high temperature resistant materials due to its highly disordered single-phase solid solution structure. In the development of high entropy materials in the past 20 years, high entropy alloy materials have been studied more, while high entropy ceramic materials have been neglected. It was not until 2015 that the concept of high entropy oxide ceramics (MgNiCoCuZn)O was proposed. After that, Gild et al. used spark plasma sintering technology to use HfB2, ZrB2, NbB2, TiB2, W2B5, CrB2, TaB2 and MoB2 as raw powders to prepare six high entropy diboride ceramics with hexagonal structure for the first time. Gild further found that any high entropy boride ceramic performed better than any diboride in terms of hardness and oxidation resistance (Science Reports, 2016, 6, 37946). Some researchers prepared high entropy monoborides with WB-type orthorhombic structure by hot pressing sintering. Research has shown that this type of high entropy boride ceramic has an ultra-high hardness of up to 48.51±4.07GPa. In addition to the ultra-high hardness, the high melting point, wear resistance and ablation resistance of high entropy boride ceramics have also been verified by the research of many scholars.
[0003] The many excellent properties of the above-mentioned high-entropy boride ceramic materials have shown great application potential in the field of surface coatings. At present, the preparation of ceramic coatings by plasma spraying technology is a relatively common method. However, in the face of the extremely high melting point and complex multi-principal materials of high-entropy ceramic materials, plasma spraying technology still has certain limitations in the preparation of high-entropy ceramic materials. In view of the difficulty of the high melting point of high-entropy ceramics, Sun et al. reduced the overall melting point of the powder by adding low-melting-point metals, thereby increasing the melting degree of the powder and reducing the porosity of the coating. However, the results show that the addition of low-melting-point metals reduces the high-temperature performance and overall hardness of the coating (Surface & Coatings Technology, 2024, 478, 130459). Tan et al. addressed the problem that the high-entropy ceramic powder composition is complex and difficult to form a ceramic solid solution. The powders were subjected to plasma spheroidization and reactive plasma spraying respectively. Although the multi-stage high-temperature heating-supercooling method reduces the porosity of the coating to a certain extent, it promotes the melting of the powder and generates a high-entropy ceramic solid solution phase. However, this method is too cumbersome and has a narrow process window (Journal of the European Ceramic Society, 2021, 41, 6772-6777). In summary, although many scholars have taken some measures, it is still difficult to break through the technical bottleneck of plasma spraying technology in the preparation of high entropy ceramic coatings. The main reason may be attributed to the low and unfocused energy of the plasma beam. Summary of the invention
[0004] The purpose of the present invention is to solve the current problems of poor forming quality of high-entropy ceramic coatings and difficulty in forming high-entropy phases due to the high melting point and complex composition of high-entropy ceramic original powders, and to provide a method for preparing high-entropy ceramic coatings on the surface of titanium alloys based on in-situ reaction of a high-speed laser cladding molten pool.
[0005] The method for preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool is implemented according to the following steps:
[0006] 1. Grinding and cleaning the surface of the titanium alloy in sequence to obtain a cleaned titanium alloy substrate;
[0007] 2. Wet-milling and mixing five or more diboride ceramic powders to obtain a diboride mixed slurry;
[0008] 3. adding a binder to the diboride mixed slurry to obtain a ceramic mixed slurry containing the binder;
[0009] 4. spraying and granulating the ceramic mixed slurry containing the binder to obtain a composite ceramic powder;
[0010] 5. Load the ceramic composite powder into the automatic powder feeder, adjust the focus of the laser beam and the powder beam to overlap below the cladding nozzle, control the laser power to 2600-3300 W, the cladding speed to 120-160 mm / s, the powder feeding rate to 1.0-1.6 r / min, the overlap rate to 70%-85%, and perform high-speed laser cladding to form a high-entropy ceramic coating on the surface of the titanium alloy.
[0011] The high entropy ceramic coating of the present invention is prepared by a high-speed laser cladding process. To ensure the fluidity of the ceramic composite powder, the powder feeder can smoothly reach the cladding nozzle during the high-speed laser cladding process. Five or more diboride ceramic powders are prepared into spherical multi-component ceramic composite powders with a size of 60 to 30 μm by spray granulation technology, which is used for the preparation of high-entropy ceramic coatings by high-speed laser cladding on the surface of titanium alloys. The high-entropy ceramic coating is generated by in-situ reaction on the surface of the titanium alloy by adjusting the high-speed laser cladding process parameters.
[0012] The present invention prepares a high-entropy ceramic coating in situ on the surface of a titanium alloy by high-speed laser cladding technology. Spherical multi-component ceramic composite powder is used as a raw material for high-speed laser cladding. The coating contains both a high-entropy monoboride phase and a high-entropy diboride phase. During the high-speed laser cladding process, all components of the ceramic powder are fully melted. There are two types of original reaction processes in the coating, the first is an in-situ reaction between the multi-component ceramic composite powder and the molten titanium alloy matrix, and the second is an in-situ replacement reaction between the multi-component ceramic composite powders. The two in-situ reactions generate high-entropy monoboride and high-entropy diboride in the coating, respectively. The internal structure of the coating is dense and does not show obvious defects. The interface between the coating and the substrate presents a good metallurgical bonding form. Thanks to the good quality of the coating and the lattice distortion effect of the high-entropy ceramic material itself, the average hardness of the coating is as high as 1931.4HV 0.5 .
[0013] The present invention proposes that the high entropy ceramic coating prepared by high-speed laser cladding on the surface of titanium alloy can be used to provide good protection and strengthening effects on the surface of titanium alloy, such as hardness, wear resistance and high-temperature oxidation resistance. The high entropy ceramic coating is generated by in-situ reaction during the high-speed laser cladding process, does not require complex powder pretreatment, has a simple preparation process, and has excellent coating quality and performance.
[0014] The present invention proposes a method for preparing a high-entropy ceramic coating on the surface of a titanium alloy by using an in-situ reaction during a high-speed laser cladding process. For a long time, there has been no suitable coating preparation technology for high-entropy ceramics due to their extremely high melting point and complex components. The high-energy laser beam of the high-speed laser cladding technology has an extremely high energy density and has a high potential in preparing high-entropy ceramic coatings. In addition, high-speed laser cladding has an extremely fast cooling rate, which can inhibit the formation of second-phase compounds in the coating, making the coating more inclined to generate a high-entropy solid solution structure. The present invention successfully generates a high-entropy ceramic coating in situ on the surface of a titanium alloy by adjusting the process parameters of high-speed laser cladding. The coating exhibits good quality: there are no defects such as pores and cracks inside; the interface presents a perfect metallurgical bond with the substrate. The phase structure of the coating is a distinct high-entropy ceramic phase, including a high-entropy monoboride phase and a high-entropy diboride phase. Thanks to the quality and phase structure of the coating, the coating exhibits extremely high hardness. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a cross-sectional morphology diagram of the titanium alloy surface clad with a high entropy ceramic coating sample 1 in Example 1;
[0016] Figure 2 This is a cross-sectional morphology diagram of sample 2 of titanium alloy surface clad with high entropy ceramic coating in Example 2;
[0017] Figure 3 This is a cross-sectional morphology of sample 3 of titanium alloy surface clad with high entropy ceramic coating in Example 3;
[0018] Figure 4 This is a cross-sectional morphology diagram of the titanium alloy surface clad with a high entropy ceramic coating sample 4 in Example 4;
[0019] Figure 5 for Figure 1 The macroscopic and microscopic morphology and element distribution of sample 1 are shown. Figure 5 (a) is the cross-sectional secondary electron macroscopic morphology of the coating. Figure 5 (b) is the microscopic morphology of the coating. Figure 5 (c1)-(c6) are element distribution diagrams of the microscopic morphology of the coating in 5(b);
[0020] Figure 6 This is the test result diagram of the phase composition of sample 3;
[0021] Figure 7 This is the test result diagram of the coating hardness distribution of sample 3. DETAILED DESCRIPTION
[0022] Specific implementation method 1: This implementation method is based on the high-speed laser cladding molten pool in-situ reaction to prepare a high-entropy ceramic coating on the surface of a titanium alloy according to the following steps:
[0023] 1. Grinding and cleaning the surface of the titanium alloy in sequence to obtain a cleaned titanium alloy substrate;
[0024] 2. Wet-milling and mixing five or more diboride ceramic powders to obtain a diboride mixed slurry;
[0025] 3. adding a binder to the diboride mixed slurry to obtain a ceramic mixed slurry containing the binder;
[0026] 4. spraying and granulating the ceramic mixed slurry containing the binder to obtain a composite ceramic powder;
[0027] 5. Load the ceramic composite powder into the automatic powder feeder, adjust the focus of the laser beam and the powder beam to overlap below the cladding nozzle, control the laser power to 2600-3300 W, the cladding speed to 120-160 mm / s, the powder feeding rate to 1.0-1.6 r / min, the overlap rate to 70%-85%, and perform high-speed laser cladding to form a high-entropy ceramic coating on the surface of the titanium alloy.
[0028] The high entropy ceramic coating of this embodiment includes two in-situ generated high entropy ceramic phases. The original multi-component ceramic composite powder is fully melted under the action of a high-energy laser beam. A portion of the molten multi-component ceramic composite powder reacts with the molten titanium alloy matrix to generate a high entropy monoboride ceramic phase, as shown in formula (1); another portion of the molten multi-component ceramic composite powder undergoes a substitution reaction to generate a high entropy diboride ceramic phase, and the high entropy diboride phase is a substitution reaction of Me atoms between each diboride MeB2. As mentioned above, the premise that the molten ceramic powder can react with the molten matrix is that the selected ceramic powder is a diboride.
[0029] 2MeB2+2Ti→2(Me,Ti)B2(1)
[0030] The high entropy coating prepared in this embodiment exhibits good metallurgical bonding at the interface with the substrate. The internal structure of the coating is dense without obvious cracks and pores. The high entropy monoboride phase exhibits a needle-like morphology and is evenly distributed in the coating, and the high entropy diboride serves as the coating skeleton.
[0031] This embodiment is based on the principle of in-situ reaction of the molten pool on the surface of the titanium alloy under a high-energy laser beam, and a high-entropy ceramic coating is prepared in situ on the surface of the titanium alloy by high-speed laser cladding technology. The high-entropy ceramic coating is prepared by a high-speed laser cladding process, based on the principle of in-situ reaction of the molten pool on the surface of the titanium alloy under a high-energy laser beam. Five or more submicron-grade ceramic powders are prepared into spherical multi-component ceramic composite powders by spray granulation technology. A high-entropy ceramic coating is prepared in situ on the surface of the titanium alloy by high-speed laser cladding technology. The cladding nozzle sprays out a spherical multi-component ceramic composite powder, and the laser beam simultaneously irradiates the spherical multi-component ceramic composite powder and the surface of the titanium alloy to form a molten pool on the surface of the titanium alloy, and a high-entropy ceramic coating is generated after an in-situ reaction in the molten pool. The high-entropy ceramic coating contains two high-entropy ceramic phases, namely a high-entropy monoboride phase and a high-entropy diboride phase. Both high-entropy ceramic phases are generated by in-situ reaction of the molten pool on the surface of the titanium alloy during high-speed laser cladding.
[0032] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that in step 1, #120 to #400 sandpaper is used to grind the surface of the titanium alloy.
[0033] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that the titanium alloy described in step one is TC4, TC9 or TC11.
[0034] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that during the wet ball milling process in step 2, the ball-to-material ratio is controlled to be 3:1, the rotation speed is 300 r / min, and the ball milling time is 10 to 15 h.
[0035] Specific embodiment 5: The difference between this embodiment and specific embodiments 1 to 4 is that the particle size of the diboride ceramic powder in step 2 is submicron level.
[0036] Specific embodiment six: The difference between this embodiment and any one of specific embodiments one to five is that the diboride ceramic powder in step two is selected from ZrB2 ceramic powder, TiB2 ceramic powder, NbB2 ceramic powder, TaB2 ceramic powder, HfB2 ceramic powder, CrB2 ceramic powder and WB2 ceramic powder.
[0037] Specific implementation method 7: This implementation method is different from any one of specific implementation methods 1 to 6 in that the binder described in step 3 is PVA with a mass fraction of 2%.
[0038] Specific embodiment eight: This embodiment differs from any one of specific embodiments one to seven in that the particle size of the composite ceramic powder in step four is 30 to 60 μm.
[0039] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that in step 4, the composite ceramic powder is dried at a temperature of 50-60°C.
[0040] Specific embodiment ten: This embodiment differs from specific embodiments one to nine in that in step five, the surface of the titanium alloy substrate to be clad is placed 1.5 to 2.5 mm below the focus.
[0041] Specific implementation eleven: This implementation differs from specific implementations one to ten in that in step five, the laser power is controlled to be 2600-3000 W, the cladding speed is 130-140 mm / s, the powder feeding rate is 1.4-1.5 r / min, and the overlap rate is 75%-85%.
[0042] Example 1: The method of preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool in this example is implemented according to the following steps:
[0043] 1. Use #120~#400 sandpaper to polish the surface of the titanium alloy to remove impurities such as oxide scale on the surface of the substrate. Then use anhydrous ethanol to ultrasonically clean the surface of the titanium alloy to remove oil stains on the surface of the substrate to obtain a cleaned titanium alloy substrate;
[0044] 2. The five diboride ceramic powders are configured as the original powders according to the table below. The five diboride ceramic powders are ZrB2 ceramic powder, TiB2 ceramic powder, TaB2 ceramic powder, MoB2 ceramic powder and NbB2 ceramic powder, respectively, and are wet-milled and mixed. The ball-to-material ratio is controlled to be 3:1, the rotation speed is 300r / min, and the ball milling time is 12h to obtain a diboride mixed slurry;
[0045]
[0046] 3. Adding 2% by mass of PVA (binder) to the diboride mixed slurry to obtain a ceramic mixed slurry containing the binder;
[0047] 4. spray granulating the ceramic mixed slurry containing the binder to obtain a spherical composite ceramic powder with a particle size of 60 to 30 μm;
[0048] 5. Load the ceramic composite powder into the automatic powder feeder, adjust the focus of the laser beam and the powder beam to overlap below the cladding nozzle, place the surface of the titanium alloy substrate to be clad 2mm below the focus, control the laser power to 2600W, the cladding speed to 130mm / s, the powder feeding rate to 1.4r / min, the overlap rate to 80%, and perform high-speed laser cladding to form a high-entropy ceramic coating on the surface of the titanium alloy.
[0049] like Figure 1It is shown that the high entropy ceramic coating prepared by this embodiment has a thickness of about 450 μm, has no obvious defects inside, and exhibits good metallurgical bonding at the interface.
[0050] The following table shows the specific parameters of the high-speed laser cladding process in this embodiment.
[0051]
[0052] Example 2: The difference between this example and Example 1 is that in step five, the ceramic composite powder is loaded into the automatic powder feeder, the focal points of the laser beam and the powder beam are adjusted to overlap below the cladding nozzle, the surface of the titanium alloy substrate to be clad is placed 2 mm below the focus, the laser power is controlled to 2200 W, the cladding speed is 130 mm / s, the powder feeding rate is 1.4 r / min, the overlap rate is 80%, and high-speed laser cladding is performed to form a high-entropy ceramic coating on the surface of the titanium alloy.
[0053] like Figure 2 As shown, there are obvious pores and unfused areas inside the coating prepared by this embodiment. This is mainly because after the laser power is reduced to 2200W, the energy density of the laser beam is reduced and the multi-component composite ceramic powder cannot be fully melted, which leads to the formation of a large number of defects in the coating. Therefore, the next step of testing is no longer carried out on Sample 2.
[0054] The following table shows the specific parameters of the high-speed laser cladding process in this embodiment.
[0055]
[0056] Example 3: This example is different from Example 1 in that in step five, the ceramic composite powder is loaded into an automatic powder feeder, the focal points of the laser beam and the powder beam are adjusted to overlap below the cladding nozzle, the surface of the titanium alloy substrate to be clad is placed 2 mm below the focus, the laser power is controlled to 2600 W, the cladding speed is 180 mm / s, the powder feeding rate is 1.4 r / min, the overlap rate is 80%, and high-speed laser cladding is performed to form a high-entropy ceramic coating on the surface of the titanium alloy.
[0057] like Figure 3 As shown, there are obvious pore defects at the interface of the coating prepared by Example 3. This is mainly because after the cladding speed is increased to 180 mm / s, the interaction between the laser beam and the substrate surface per unit time is weakened, resulting in the formation of large-sized holes at the coating interface, so the next step of testing is not performed on Sample 3.
[0058] The following table shows the specific parameters of the high-speed laser cladding process in this embodiment.
[0059]
[0060] Example 4: This example is different from Example 1 in that in step five, the ceramic composite powder is loaded into an automatic powder feeder, the focal points of the laser beam and the powder beam are adjusted to overlap below the cladding nozzle, the surface of the titanium alloy substrate to be clad is placed 2 mm below the focus, the laser power is controlled to 2600 W, the cladding speed is 130 mm / s, the powder feeding rate is 1.8 r / min, the overlap rate is 80%, and high-speed laser cladding is performed to form a high-entropy ceramic coating on the surface of the titanium alloy.
[0061] like Figure 4 As shown, there are obvious defects inside and at the interface of the coating prepared by Example 4. This is mainly because after the powder feeding rate increases, the barrier effect of the powder beam on the laser beam becomes more obvious, weakening the interaction between the laser beam and the substrate surface. In addition, the increase in the powder feeding rate also increases the difficulty of the laser beam to fully melt the multi-component composite ceramic powder, resulting in obvious unfused areas inside the coating, so Sample 4 is no longer tested in the next step.
[0062] The following table shows the specific parameters of the high-speed laser cladding process in this embodiment.
[0063]
[0064] The raw materials and equipment used in the above examples are as follows:
[0065] 1. ZrB2 ultrafine powder was purchased from Nangong Jingrui Alloy Products Co., Ltd. with a particle size of 0.5-1.0 μm and a purity of 99.5%.
[0066] 2. TiB2 ultrafine powder was purchased from Nangong Jingrui Alloy Products Co., Ltd. with a particle size of 0.5-1.0 μm and a purity of 99.5%.
[0067] 3.TaB2 ultrafine powder was purchased from Nangong Jingrui Alloy Products Co., Ltd. with a particle size of 0.5-1.0 μm and a purity of 99.5%.
[0068] 4. MoB2 ultrafine powder was purchased from Nangong Jingrui Alloy Products Co., Ltd. with a particle size of 0.5-1.0 μm and a purity of 99.5%.
[0069] 5. NbB2 ultrafine powder was purchased from Nangong Jingrui Alloy Products Co., Ltd. with a particle size of 0.5-1.0 μm and a purity of 99.5%.
[0070] 6. Titanium alloy was purchased from Taizhou Qianzhan Metal Products Co., Ltd.
[0071] 7. RC-LCD-4000-IPG high-speed laser cladding system was purchased from Nanjing Zhongke Yuchen Laser Technology Co., Ltd.
[0072] The high entropy ceramic coating (sample 1) prepared on the titanium alloy surface in Example 1 was tested:
[0073] The aluminum alloy with coating after cladding was cut into 10×10×10mm samples by electric spark cutting. Sample 1 was polished to a mirror surface for observation. Figure 1 It can be seen that the internal structure of the coating is dense, and the interface and the substrate show a complete metallurgical bond. The microscopic morphology and phase composition of the coating are further observed using an electron microscope and an XRD multifunctional X-ray diffractometer to determine whether the coating is a high-entropy ceramic coating. Figure 5 (a) is a scanning electron microscope image of the coating cross section. The coating has a dense structure and no obvious defects such as pores and cracks. The coating and the substrate show a perfect metallurgical bond. Further zoom in on the selected area in Figure (a), as shown in the figure below. Figure 5 (b) The grains inside the coating present an obvious pillow-like structure. The element distribution test of Figure (5) shows that: on the one hand, there is no aggregation of single B and Me elements in the coating, which indicates that there is no single boride phase in the coating, which indicates that the original diboride powder was melted and reacted under the action of the high-energy laser beam; on the other hand, the elements in the coating show aggregation, among which Mo and Ta elements aggregate inside the grains, while Zr, Nb, and Ti aggregate outside the grains. It is speculated that the coating may be composed of two phases: (Mo, Ta, Ti)-aggregated high-entropy ceramic phase and (Zr, Nb, Ti)-aggregated high-entropy ceramic phase. The XRD experimental data analysis of the coating verified the above conjecture. There are two high-entropy ceramic phases in the coating, one is a high-entropy monoboride aggregated by (Mo, Ta, Ti), and the other is a high-entropy diboride aggregated by (Zr, Nb, Ti). Figure 5 The relative content of Me element was detected in the area shown in (b), and three points were taken inside and outside the grain to test and the average values inside and outside the grain were calculated. The test results are shown in the following table. It further confirms that the elements in the coating are segregated and there are two high entropy ceramic phases.
[0074]
[0075] The coating was subjected to matrix hardness testing, with a total of 15 points tested. The test results are as follows: Figure 7 As shown. The average hardness of the coating is as high as 1931.4HV 0.5 , the highest hardness can reach 2090HV 0.5 This is mainly due to the dense internal structure of the coating and the inherent lattice distortion effect of high entropy ceramic materials.
[0076] In summary, the present invention provides a method for preparing a high-entropy ceramic coating on the surface of a titanium alloy. A high-entropy ceramic coating with good coating quality can be obtained within the scope defined by the present invention. When the laser power exceeds the defined range of the present invention, the ceramic powder will not be fully melted, which will lead to a large number of holes in the coating. When the cladding speed exceeds the defined range of the present invention, a large number of defects will appear at the coating interface. In addition, when the powder feeding rate exceeds the defined range of the present invention, a large number of defects will also appear in the coating. These obvious defects are great hidden dangers during the service of the coating, reducing the protective effect of the coating on the titanium alloy. A high-entropy ceramic coating with good quality can be obtained on the surface of the titanium alloy within the process range defined by the present invention.
[0077] The method provided by the present invention for in-situ preparation of a high-entropy ceramic coating on a titanium alloy surface by high-speed laser cladding is mainly aimed at the shortcomings of the current preparation methods of high-entropy ceramic coatings and the protection of the titanium alloy surface. A high-entropy ceramic coating containing both a high-entropy monoboride and a high-entropy diboride is generated by in-situ reactions between multi-component composite ceramic powders and between the matrix and the multi-component ceramic powders during the high-speed laser cladding process. The method of the present invention can prepare a high-entropy ceramic coating with good quality and high hardness, which can well solve the current preparation problems of high-entropy ceramic coatings and the protection problems of titanium alloy surfaces.
Claims
1. A method for preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool, characterized in that The method for preparing a high entropy ceramic coating on a titanium alloy surface is achieved by the following steps:
1. Grinding and cleaning the surface of the titanium alloy in sequence to obtain a cleaned titanium alloy substrate; 2. Wet-milling and mixing five or more diboride ceramic powders to obtain a diboride mixed slurry; 3. adding a binder to the diboride mixed slurry to obtain a ceramic mixed slurry containing the binder; 4. spraying and granulating the ceramic mixed slurry containing the binder to obtain a composite ceramic powder; 5. Load the composite ceramic powder into the automatic powder feeder, adjust the focus of the laser beam and the powder beam to overlap below the cladding nozzle, control the laser power to 2600-3300 W, the cladding speed to 120-160 mm / s, the powder feeding rate to 1.0-1.6 r / min, the overlap rate to 70%-85%, and perform high-speed laser cladding to form a high-entropy ceramic coating on the surface of the titanium alloy.
2. The method for preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool according to claim 1 is characterized in that In step 1, use #120 to #400 sandpaper to polish the surface of the titanium alloy.
3. The method for preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool according to claim 1 is characterized in that The titanium alloy described in step 1 is TC4, TC9 or TC11.
4. The method for preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool according to claim 1 is characterized in that During the wet ball milling process in step 2, the ball-to-material ratio is controlled to be 3:1, the rotation speed is 300 r / min, and the ball milling time is 10 to 15 h.
5. The method for preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool according to claim 1 is characterized in that The particle size of the diboride ceramic powder in step 2 is submicron level.
6. The method for preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool according to claim 1 is characterized in that In step 2, the diboride ceramic powder is selected from ZrB2 ceramic powder, TiB2 ceramic powder, NbB2 ceramic powder, TaB2 ceramic powder, HfB2 ceramic powder, CrB2 ceramic powder and WB2 ceramic powder.
7. The method for preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool according to claim 1 is characterized in that The binder described in step three is PVA with a mass fraction of 2%.
8. The method for preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool according to claim 1 is characterized in that The particle size of the composite ceramic powder in step 4 is 30-60 μm.
9. The method for preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool according to claim 1, characterized in that In step 4, the composite ceramic powder is dried at a temperature of 50-60°C.
10. The method for preparing a high entropy ceramic coating on a titanium alloy surface based on an in-situ reaction of a high-speed laser cladding molten pool according to claim 1, characterized in that In step five, the laser power is controlled to be 2600-3000 W, the cladding speed is 130-140 mm / s, the powder feeding rate is 1.4-1.5 r / min, and the overlap rate is 75%-85%.